2018
DOI: 10.1016/j.jbusres.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Family incivility, emotional exhaustion at work, and being a good soldier: The buffering roles of waypower and willpower

Abstract: This study unpacks the relationship between family incivility and organizational citizenship behavior (OCB), suggesting a mediating role of emotional exhaustion and moderating roles of waypower and willpower, two critical dimensions of hope. Three-wave data from employees and their peers in Pakistani organizations show that an important reason that family incivility diminishes OCB is that employees become emotionally overextended by their work.Employees' waypower and willpower buffer this harmful effect of fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 83 publications
(189 reference statements)
6
76
1
1
Order By: Relevance
“…The current study established a positive association between family incivility and emotional exhaustion, which validates the existing literature propositions and findings (Anand, Vidyarthi, Singh & Ryu, 2015;Cooke & Rousseau, 1984;De Clercq, Haq, Azeem & Raja, 2018;Zhang, Griffeth & Fried, 2012). The current empirical findings validate that emotional exhaustion has a negative association with thriving.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The current study established a positive association between family incivility and emotional exhaustion, which validates the existing literature propositions and findings (Anand, Vidyarthi, Singh & Ryu, 2015;Cooke & Rousseau, 1984;De Clercq, Haq, Azeem & Raja, 2018;Zhang, Griffeth & Fried, 2012). The current empirical findings validate that emotional exhaustion has a negative association with thriving.…”
Section: Discussionsupporting
confidence: 86%
“…A recent study confirms that workplace incivility leads to hostility (Lim, Ilies, Koopman, Christoforou & Arvey, 2018). However, employees are most likely to spill over the experience of stress in one domain and have a negative impact on their functioning in another domain such as stress from family affects workplaces badly (De Clercq, Haq, Azeem, & Raja, 2018). In this regard, the work of Ain (2017) is relevant, who studied the mediation mechanism of aggression between family incivility and counterproductive work behaviors.…”
Section: H1 (I) Family Incivility Has a Negative Relationship With Thmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, family incivility has ambiguous purposes, which stands apart from other constructs such as family undermining and aggression that involve intentional harmful actions (i.e., verbally or physically threatening behavior) (Hoobler & Brass, ; Kiewitz et al, ; Tepper, ). Recent research has shown that the minor unfavorable events such as family incivility create daily hassles or anxiety, making the family environment toxic and posing an even greater impact on health and well‐being of a targeted person (Bai et al, ; De Clercq et al, ; Lim & Tai, ). Considering these findings, it is worth studying individuals’ exposure to incivility at home that drives their behavioral reaction.…”
mentioning
confidence: 99%
“…Similarly, unpleasant life events, life imbalances, andincreased conflicts within the domains of work and family can also be a cause of creating emotional exhaustion (Karatepe 2013;Chen et al, 2018). Such exhausted behavior then put serious negative effects on health, job performance, and organizational commitment of the employees (Servellen, Topf, &Leake, 1994;Wright &Cropanzano, 1998;Moon &Hur, 2011;Hur et al, 2015;Collie, Granziera, & Martin, 2018).Emotional disorder also produce counterproductive work behavior, reduce organizational citizenship behavior, and enhance turnover intentions of employees (Raman, Sambasivan, & Kumar, 2016;De Clercq, InamUlHaq, Azeem, & Raja, 2018;Alola, Olugbade, Avci, &Ozturen, 2019).…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%